Pengaruh Penggunaan Media Powerpoint Terhadap Minat dan Hasil Belajar Siswa - Lalu Muhammad Nasir; Akhmad Jamiludin (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2023)
Learning media has a considerable influence in the learning process. on interest in learning and student learning outcomes in science learning. This type of research is a quantitative research design with a Quasi-experiment design: One-Group Pre-test-Post-test Design with one type of treatment. The research design used Pre-test-Post-test Design. The subjects of this study were all grade IV B students of SD Negeri Teratak in the 2021/2022 academic year. The data obtained consisted of data on interest in learning scores and scores of science learning outcomes for experimental group students. The instrument used is a learning interest questionnaire and a science learning outcome test. The data were analyzed to determine the effect of Powerpoint media on students' interest in learning and student learning outcomes based on pretest and post-test in the experimental group. Interest in learning science in grade IV SD Negeri Teratak increased by 67.65%, namely from the result of the difference in the percentage before learning and after learning. Meanwhile, the science learning outcomes of the fourth grade students of SD Negeri Teratak increased by 52.94% from the difference in the percentage before and after learning. There is an influence of Power-point media on learning interest and science learning outcomes for class IVB students at SD Negeri Teratak in the 2021/2022 academic year.